2002
DOI: 10.1097/00004872-200206000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone acts on the kidney, not the brain, to cause mineralocorticoid hypertension in sheep

Abstract: In conscious sheep the hypertensive response to aldosterone resulted from an action on the kidney, with no evidence for a direct action on the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These findings are consistent with previous studies in rats by Gomez-Sanchez and Gomez-Sanchez (10). In contrast, chronic intracerebroventricular infusion of aldosterone in sheep did not change BP (22). The latter studies used regular aCSF, and it is tempting to speculate that sheep also may respond to intracerebroventricular aldosterone if combined with a small increase in CSF Na ϩ .…”
Section: Discussionmentioning
confidence: 97%
“…These findings are consistent with previous studies in rats by Gomez-Sanchez and Gomez-Sanchez (10). In contrast, chronic intracerebroventricular infusion of aldosterone in sheep did not change BP (22). The latter studies used regular aCSF, and it is tempting to speculate that sheep also may respond to intracerebroventricular aldosterone if combined with a small increase in CSF Na ϩ .…”
Section: Discussionmentioning
confidence: 97%
“…32 Furthermore, inhibition of sympathetic activity has also been reported following induction of mineralocorticoid hypertension in dogs, sheep, and humans. 19,33–34 Of particular relevance to primary aldosteronism, several studies 18,20,35 but not all, 22 have reported either normal or suppressed levels of sympathetic activity in this form of secondary hypertension. Also the present study does not provide statistically significant evidence to support the hypothesis of sympathetic activation in aldosterone hypertension, in fact, even showing a small statistically insignificant reduction in plasma levels of NE during aldosterone infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental and clinical studies indicate that mineralocorticoid-induced hypertension is not associated with increased sympathetic activity (9,46,55,57,59 Time (Days) 62 …”
Section: Additive Blood Pressure-lowering Effects Of Renal Denervatiomentioning
confidence: 99%